CLONAL PROSPECTION AND VIRUSES OCCURRENCE IN THE GRAPEVINE CV. ‘FOLHA DE FIGO’, AT CALDAS, MG, BRAZIL - VILLA, Fabíola; REGINA, Murillo de Albuquerque; ALVARENGA, Ângelo Albérico; PASQUAL, Moacir; STOPA, Regiane Abjaud (Scientia Agraria, 2010)
The productivity of grapevine (Vitis labrusca L.) cv. Folha de Figo in the region of Caldas, Minas Gerais state, Brazil, is very low, due to, among others factors, the occurrence of viruses. In this study we selected and evaluated the genetic similarity of this cultivar and surveyed possible viruses present in these plants. This work started in 1994 at EPAMIG’s vineyard and private orchards, where a first selection was proceeded from 137 plants, obeying the vegetation visual criteria, production and varietal identity. These had been marked for the accompaniment of the volume and quality of the production. During the spring of 1996, before the harvest, during the beginning of the maturation of the clusters, it was initiated the works of massal selection and defined as parameter of this selection the production for plant and the fertility index. The DAS-ELISA test was carried out to verify the detect possible viruses in 19 selected clones. There were detected only the Grapevine virus A (GVA) and Grapevine leafroll associated virus 3 (GLRaV-3) in 16% and 47% of the tested plants, respectively. The infected plants, however, presented the average productions better than 5.0 kg plant-1 (13,29 t ha-1), revealing that these viruses had little effect on the yield.